Horizontal laminar flow cabinet with a low background and clean air - Tomasz Samborski; Andrzej Zbrowski; Stanisław Kozioł (Technologia i Automatyzacja Montażu)
The publication presents the design, construction of a prototype, and the course of verification tests of a special horizontal laminar flow cabinet made entirely of plastics. In the cabinet design process, numerical simulations and airflow analyses were used to achieve a laminar, uniform flow in the device's workspace. A prototype was built and subjected to verification tests regarding the intensity and nature of airflow as well as air cleanliness. The cabinet is equipped with its own filtration-ventilation module providing clean air to the workspace and removing used air to the external ventilation system. It ensures an increased level of protection for workers dealing with microorganisms and hazardous airborne chemicals, as well as complete corrosion resistance inside the workspace. A particular area of application for the cabinet is research involving radionuclides, volatile, toxic chemical compounds for which air-recirculating devices cannot be used in the room where they are placed. The developed solution has been protected by industrial property rights and used to implement a contract for the supply of a set of equipment to the laboratory of the Institute of Nuclear Physics of the Polish Academy of Sciences.